What Role for Public Participation in Implementing the EU Floods Directive? A Comparison With the Water Framework Directive, Early Evidence from Germany and a Research Agenda. (23rd May 2014) - Newig, Jens; Challies, Edward; Jager, Nicolas; Kochskämper, Elisa
ABSTRACT We examine the roles and functions of non‐state actor participation in implementing the EU Floods Directive of 2007 (FD). We draw on experiences with participation under the Water Framework Directive (WFD), because of important links between the two directives. Comparing the legal bases and the different functions for participation, we observe the paradoxical situation that while the WFD has fervently advocated public participation public interest has remained low, whereas the FD is less sanguine about participation despite citizens being potentially more affected by flood management issues – particularly given the current trend towards a 'risk management' approach under the FD. Our examination of current FD implementation in Germany reveals a considerable variety of participation approaches, as well as a general trend to 'less' rather than 'more' participation as compared with the WFD. The paper closes by discussing implications for future flood management planning and avenues for comparative research. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment